Thermally stimulated currents of Zn-Bi-0 thin film arresters - Gubanski, A.; Ziaja, J.; Mista, W. (Functional Materials, 2004)
Ceramic varistors based on zinc oxide have excellent properties as protection devices used in power industry. However, their breakdown voltage, dependent on number of grain boundaries, is too high for use in electronic applications. In this work, performance of micro-devices having varistor-type current-voltage characteristics with low breakdown voltage is reported. The thermally stimulated depolarisation current (TSDC) technique was used to study the dielectric relaxation of the Zn-Bi-0 thin-film arresters. The surface varistor layers were prepared by r.f. magnetron sputtering on nickel support. The TSDC measuring system and cryostat apparatus used in experiment have been described.